2018
DOI: 10.1039/c7en00740j
|View full text |Cite
|
Sign up to set email alerts
|

Sex dependent effects of silver nanoparticles on the zebrafish gut microbiota

Abstract: Silver nanoparticles (AgNPs), the most prevalent commercial nanomaterial products, are widely released into the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…To take an example, male zebrafish were more susceptible to the NMs' exposure, compared to female zebrafish. [114] In addi tion, freshly prepared Ag NMs gave rise to more serious toxicity on gut microbiota due to the release of higher concentration of Ag + than that of stale Ag NMs. [112] In a recent work, to delin eate the antibacterial mechanism of silver nanomaterials, we compared the antibacterial activity of Ag NMs against two ben eficial lactobacilli (Lactobacillus delbrueckii subsp.…”
Section: Effects Of Nanomaterials On Gut Microbiotamentioning
confidence: 99%
“…To take an example, male zebrafish were more susceptible to the NMs' exposure, compared to female zebrafish. [114] In addi tion, freshly prepared Ag NMs gave rise to more serious toxicity on gut microbiota due to the release of higher concentration of Ag + than that of stale Ag NMs. [112] In a recent work, to delin eate the antibacterial mechanism of silver nanomaterials, we compared the antibacterial activity of Ag NMs against two ben eficial lactobacilli (Lactobacillus delbrueckii subsp.…”
Section: Effects Of Nanomaterials On Gut Microbiotamentioning
confidence: 99%
“…Sex is documented to influence both gut microbiota composition (Bolnick et al 2014;Haro et al 2016), as well as the microbiome responses. Exposure to silver nanoparticles was for example shown to modify the gut microbiota structure of male but not female zebrafish (Ma et al 2018). Interestingly, sex-differentiated responses to compounds are also commonly reported in classical toxicology studies, for example in medaka fish exposed to cyanotoxins (Le Manach et al 2016).…”
Section: Correlation Versus Causality: Confounding Factors Should Notmentioning
confidence: 83%
“…The result showed that the taxonomic information of total samples was 18 Phyla, 34 Classes, 87 Orders, 144 Families, 247 Genera, 324 Species, and 406 OTUs. According to our previous studies [23,37], the composition and functions of intestinal microbiota in female and male zebrafish were different, thus the following analysis of each group was departed by gender. The groups were marked by female and male in control (F-0 and M-0), female and male in 100 μg/L DEHP group (F-100 and M-100).…”
Section: Diversity and Richness Of Intestinal Microbiota In Adult Zebmentioning
confidence: 99%
“…The intestinal microbiota of male and female zebrafish was detected via the high-throughput sequencing, and the analysis methods were performed according to previous reports [23,37]. Briefly, the total genomic DNA of intestinal samples was extracted and purified with FastDNA ® SPIN Kit for Soil (Mpbio, USA).…”
Section: The Analysis Of Zebrafish Intestinal Microbiota By 16s Rrna mentioning
confidence: 99%
See 1 more Smart Citation